2019
DOI: 10.1101/gr.242032.118
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting roles of the RSC and ISW1/CHD1 chromatin remodelers in RNA polymerase II elongation and termination

Abstract: Most yeast genes have a nucleosome-depleted region (NDR) at the promoter and an array of regularly spaced nucleosomes phased relative to the transcription start site. We have examined the interplay between RSC (a conserved essential SWI/SNFtype complex that determines NDR size) and the ISW1, CHD1, and ISW2 nucleosome spacing enzymes in chromatin organization and transcription, using isogenic strains lacking all combinations of these enzymes. The contributions of these remodelers to chromatin organization are l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
111
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(123 citation statements)
references
References 63 publications
12
111
0
Order By: Relevance
“…To test the above prediction, we examined the Pol II ChIP-seq data from isogenic WT and Rsc8depleted cells (rsc8), published by Clark and colleagues (Ocampo et al, 2019). We observed that the reductions in Pol II occupancies upon Rsc8 depletion were greatest at genes displaying the highest Pol II occupancies in WT cells, genome-wide ( Figure 4D and 4E).…”
Section: Ablating Rsc Transcription Of Highly Transcribed Genesmentioning
confidence: 86%
See 4 more Smart Citations
“…To test the above prediction, we examined the Pol II ChIP-seq data from isogenic WT and Rsc8depleted cells (rsc8), published by Clark and colleagues (Ocampo et al, 2019). We observed that the reductions in Pol II occupancies upon Rsc8 depletion were greatest at genes displaying the highest Pol II occupancies in WT cells, genome-wide ( Figure 4D and 4E).…”
Section: Ablating Rsc Transcription Of Highly Transcribed Genesmentioning
confidence: 86%
“…Consistent with this, loss of RSC function resulted in NDR filling genome-wide in a manner independent of transcription status ( Figures 4C-4E). Immunoprecipitation-independent methods such as "CUT&RUN" (Skene and Henikoff, 2017) and ChEC-seq have shown that RSC localizes to -1 and +1 nucleosomes for the majority of genes, and that RSC loss leads to the movement of -1 and +1 nucleosomes towards NDRs genome-wide (Brahma and Henikoff, 2019;Klein-Brill et al, 2019;Kubik et al, 2019;Kubik et al, 2018;Ocampo et al, 2019;Parnell et al, 2015). These methods detected RSC signal at more genes than conventional ChIP, providing evidence that RSC may indeed interact transiently with promoter nucleosomes at these genes.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations